Efficacy and safety of ocrelizumab in patients with relapsing‐remitting multiple sclerosis with suboptimal response to prior disease‐modifying therapies: A primary analysis from the phase 3b CASTING single‐arm, open‐label trial. (25th November 2021) - Vermersch, Patrick; Oreja‐Guevara, Celia; Siva, Aksel; Van Wijmeersch, Bart; Wiendl, Heinz; Wuerfel, Jens; Buffels, Regine; Kadner, Karen; Kuenzel, Thomas; Comi, Giancarlo; ,
Abstract: Background and purpose: Using the treatment goal of "no evidence of disease activity" (NEDA) incorporating magnetic resonance imaging (MRI) re‐baselining, we aimed to assess the efficacy of ocrelizumab in patients with relapsing‐remitting multiple sclerosis with a prior suboptimal response, defined by MRI or relapse criteria, to one or two disease‐modifying therapies (DMTs). Methods: CASTING was a prospective, international, multicenter, single‐arm, open‐label phase 3 trial (NCT02861014). Patients (Expanded Disability Status Scale [EDSS] score ≤ 4.0, with discontinued prior DMT of ≥6 months duration due to suboptimal disease control) received intravenous ocrelizumab 600 mg every 24 weeks for 96 weeks. The primary endpoint was NEDA (defined as absence of relapses, disability progression, and inflammatory MRI measures, with prespecified MRI re‐baselining at Week 8) over 96 weeks. Results: A total of 680 patients were enrolled, 167 (24.6%) based on MRI activity only. At Week 96, 74.8% (95% confidence interval [CI] 71.3–78.0, n / N = 492/658) of patients had NEDA. NEDA was highest among patients enrolled due to MRI activity alone (80.6% [95% CI 68.6–89.6], n / N = 50/62) versus those enrolled for relapse (75.1% [95% CI 69.0–80.6], n / N = 172/229) or for relapse with MRI (70.5% [95% CI 60.0–79.0], n / N = 74/105). NEDA across subgroups was highest in patients with a baseline EDSS score <2.5 (77.2% [95% CI 72.8–81.2], n / N = 315/408). NEDA was higher in patients receiving one prior DMT (77.6% [95% CI 73.2–81.6], n / N = 312/402) versus two prior DMTs (70.3% [95% CI 64.3–75.8], n / N = 180/256). Conclusions: In patients switching therapy due to suboptimal disease control, treatment with ocrelizumab led to an overall high NEDA rate across a wide range of disease‐related and demographic subgroups, regardless of prior treatment background, with no new safety signals detected. Abstract : Data from the phase IIIb CASTING trial in patients with relapsing‐remitting multiple sclerosis with a suboptimal response to one or two prior DMTs shows that switching to ocrelizumab led to a high proportion of patients with no evidence of disease activity (NEDA; defined as absence of relapses, disability progression, and inflammatory MRI measures, with prespecified magnetic resonance imaging re‐baselining at Week 8) at the end of the 96‐week treatment period.